(untitled) (Confluenţe Bibliologice, 2019)
The postage stamp issue “Cecilia Cutescu-Storck 140th anniversary of her birth”, which Romﬁlatelia introduced into circulation on March 14th, 2019 is dedicated to the celebration of the life and personality of the ﬁrst female professor of decorative arts in Romania, also noted as the ﬁrst female teacher at a State Art University in Europe. She left a remarkable artistic heritage.